Tendinitis of the wrist - le Viet, D. (1997)
On causes, types and treatments of tendinitis of the wrist, esp. in tennis players: - Tendinitis of the radial muscles - Intersection syndrome - Tendinitis of the extensor carpi ulnaris (ECU).